Vaginal microflora in ewes after estrus synchronization with intravaginal sponges: Sulake Fadhil Abbas Al-Zubaidi1; Zina Bakir Abdul-Hussain2 and Iman Fadhil Abdul-Hussain3 - Al-Zubaidi, Sulake Fadhil Abbas (The Iraqi Journal of Veterinary Medicine, 2018)
The aims of this study were to detect the changes in microflora and incidence of vaginitis in ewes after using of intravaginal sponges. Twenty five Awasi ewes were divided randomly into two groups (1st group included 9 animals and 2nd group included 16 animals). Both groups were treated with intravaginal sponges (20 mg) for 12 and 10 days respectively. Swabs were taken from vagina before insertion of sponges and immediately after sponges’ removal. The results showed that, only 2 ewes in 1st group exhibited estrus while all ewes in 2nd group exhibited estrus. Escherichia coli was the most predominant bacteria before insertion and withdrawal of sponges (66.66 and 68%) respectively. Four from nine ewes in 1st group, whereas only one ewe in 2nd group revealed vaginitis. It was concluded that intravaginal sponges do not change microflora in the vagina plainly but may cause vaginitis.